Digitalisasi Marketing Untuk Mendorong Kemandirian dan Kesejahteraan Pengusaha Keripik Pare Dilem Mojokerto - Irianto, Apri; Mukhtar, M. Nushron Ali; Kurniawan, Widiar Onny; Sawitri, Aristha Purwanthari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
This service program aims to increase the independence and welfare of bitter melon chip entrepreneurs in Dilem Village, Mojokerto through digitalization marketing. Entrepreneurs in this village face challenges in expanding the market due to limited knowledge about digital technology. The program began with a survey to identify the digital skill levels of entrepreneurs, which showed that most still rely on traditional marketing methods. In response, intensive training was provided, covering the use of social media, e-commerce platforms, as well as digital marketing strategies and content marketing. Based on the results of the survey, the service team conducted training and assistance regarding marketing digitalization. The results of the program show a significant increase in digital skills among entrepreneurs, characterized by the active use of social media and e-commerce in marketing their products. In addition, sales volume is increasing, which has a positive impact on the economic well-being of entrepreneurs. Digitalization marketing is effective in expanding the market and increasing the competitiveness of local products. This program provides a model that can be adapted by other small and medium entrepreneurs to support the independence and economic welfare of bitter melon chip entrepreneurs in Dilem Mojokerto Regency.